Uterine artery embolization in the management of postpartum hemorrhage - Hassan Elbiss; Shamsa Al Awar; Jamal Koteesh; Howaida Khair; Sara Maki; Dana H. Abdalla; Fikri M. Abu-Zidan (World Journal of Emergency Surgery)
Abstract Background Postpartum hemorrhage (PPH) is one of the leading preventable causes of maternal morbidity and mortality causing one-fourth of all maternal deaths. We aimed to study the role of uterine artery embolization (UAE) in controlling PPH and its impact on the need for hysterectomy. Methods We studied patients who were diagnosed with primary PPH between February 2012 and March 2020 at Al Ain Hospital, United Arab Emirates. We studied the characteristics and outcomes of those undergoing interventional radiology via UAE. Logistic regression analysis was done to define the factors that predict the need for emergency UAE. Results Out of 79 patients who had elective (n = 53) or emergency (n = 26) embolization, the placenta previa accreta (69.8% vs. 23.1%) and placenta previa (24.4% vs. 3.8%) were the common indications for elective versus emergency UAE (p < 0.001). The indication for UAE was the most significant factor for predicting an emergency procedure (p = 0.002) with placenta previa being significantly different from other indications (p < 0.001). Bleeding stopped in 78/79 patients (success rate of 98.7%) following UAE. Those who failed stopping of the bleeding were similar between the elective and emergency IR, (1/53 (1.9%) compared with 0/26 (0%), p = 0.99 Fisher’s Exact test). Overall, eight patients (10%) had hysterectomy, one of them was needed as the final solution to stop bleeding. There were no maternal deaths. Conclusions Interventional radiological UAE is very efficient in controlling postpartum hemorrhage. It should be recommended as the first line of treatment for significant bleeding when expertise and facilities are available. It increases survival, reduces hysterectomy rate, without a difference if done as an emergency or elective procedure.